Metagenomic data of bacterial communities associated with Acropora species from Phu Quoc Islands, Vietnam - Duong Huy Nguyen; Nhat Huy Chu; Yvan Bettarel; Jean-Christophe Auguet; Thierry Bouvier; Ha Hoang Chu; Van Ngoc Bui (Data in Brief, 2023)
Abtract: Acropora is one of the most common coral genera found in Phu Quoc Islands, Vietnam. However, the presence of marine snails, such as the coralllivorous gastropod Drupella rugosa, was a potential threat to the survival of many scleractinian species, leading to changes in the health status and bacterial diversity of coral reefs in Phu Quoc Islands. Here, we describe the composition of bacterial communities associated with two species of Acropora (Acropora formosa and Acropora millepora) using the Illumina sequencing technology. This dataset includes 5 coral samples of each status (grazed or healthy), which were collected in Phu Quoc Islands (9°55′20.6″N 104°01′16.4″E) in May 2020. A total of 19 phyla, 34 classes, 98 orders, 216 families and 364 bacterial genera were detected from 10 coral samples. Overall, Proteobacteria and Firmicutes were the two most common bacterial phyla in all samples. Significant differences in the relative abundances of the genera Fusibacter, Halarcobacter, Malaciobacter, and Thalassotalea between grazed and healthy status were observed. However, there was no differences in alpha diversity indices between the two status. Furthermore, the dataset analysis also indicated that Vibrio and Fusibacter were core genera in the grazed samples, whereas Pseudomonas was the core genus in the healthy samples.